Impact of nanoparticles stability on rheology, interfacial tension, and wettability in chemical enhanced oil recovery: A critical parametric review - Lashari, N. (Elsevier B.V., 2022)
Nanoparticles are extensively used at lab scale to improve physicochemical characteristics like interfacial tension, wettability, rheological behavior in different hydrocarbon recovery processes. Nevertheless, stability in the base fluid is the main limitation in chemical enhanced oil recovery for field implementation. The instability of nanofluids contributes to deteriorating characteristics of injectant fluid efficiency over time. This review deals with various facets of nanofluid stabilization, from the preparation stage until practical application. Specific stability aspects are investigated in terms of aggregation state, composition, shape, size, and surface chemistry. Following that, techniques for enhancing nanoparticle stability are outlined and linked to these same nanoparticle attributes. Methods for evaluating and modeling nanoparticles stability in terms of physiochemical characteristics are described. The aggregation state influences the stability of solution-phase nanoparticles. Thus, nanofluid stability as a feature of system parameters in a range of nano-hybrid applications and the relationship between nanoparticle stability and the physical/chemical properties of nanoparticles is discussed. Finally, the problems and possibilities in comprehending what nanoparticle stability entails are discussed to aid future research with this novel class of materials. Â© 2022 Elsevier B.V.